Pre-play learning and the preference reversal phenomenon - Kim, Younjun; Hoffman, Elizabeth (Southern Economic Journal, 2018)
Elicited preference rankings for two lotteries are typically inconsistent across choice and pricing tasks. We test whether pre-play learning makes preference rankings consistent. Pre-play learning denotes ex-ante lottery learning, where subjects observe playing lotteries before making decisions. We find that pre-play learning makes the average selling prices for the p-bet, of subjects who choose the p-bet, higher than their average selling prices for the $-bet. However, pre-play learning is not strong enough to equalize the rates of standard and non-standard reversals, although pre-play learning reduces the rate of standard reversals.
Keywords: C91; D12; D81; dept.eco; peer-reviewed

Emission tax and market power - Yoon, Sang Won (Atlantic Economic Journal, 2018)
Keywords: L13; Q00; dept.eco; peer-reviewed

Inflation targeting and monetary policy rules - Patalinghug, Jason C. (Global Economic Observer, 2018)
This paper examines the literature to try to explain the concept of inflation targeting. There are at present two competing monetary policy rules: (1) targeting rules and (2) instrument rules. The objective of this paper is to review the relative merits of these two monetary policy rules. The debate between using either an inflation targeting rule or an instrument rule debate displays the lack of consensus among economists concerning the proper specification and underlying assumptions of the inflation-targeting model which is suited for the analysis of key monetary policy issues. The paper also examines what recent studies have found about the effect of inflation targeting on emerging markets. These studies have shown that inflation targeting has been largely beneficial to emerging markets.
Keywords: Central Bank; Instrument Rules; Macroeconomics; dept.eco; peer-reviewed; ⛔ No DOI found

On the impossibility of sustainable growth in a manufacturing based economy - Yoon, Sang Won; Yoon, Chang-Ho (Economic Research-Ekonomska Istraživanja, 2018)
This paper investigates a possibility of sustainable growth in a multi-output endogenous growth framework where the capital accumulation takes place mainly through the production of the dirty manufactured goods. It is shown that in a closed economy, economic growth is not environmentally sustainable, even under an optimal pollution tax unless the consumption elasticity of substitution between clean and dirty goods approaches infinity as in a small open economy which exports dirty goods. There exists a minimal threshold level of the ratio of clean to dirty capital that ensures sustainable growth in a closed economy.
Keywords: Kuznets curve; Sustainable growth; consumption behavior; dept.eco; economic growth; elasticity; elasticity of marginal utility; elasticity of substitution; environmental Kuznets curve; peer-reviewed; sustainable development

Economic nationalism in the history of international economics - Grubacic, Sanja; Schuster, Julian (International Journal of Pluralism and Economics Education, 2018)
This paper examines the sources of economic nationalism by a closer examination of the theory and policy of international trade, originating in the 19th century. We compare and contrast the views of British classical writers, the main proponents of trade liberalism, with the writings of Friedrich List, the main proponent of economic nationalism. The focus is on the distributional implications of trade, and the treatment of the benefits that a poor country may derive from trading with a rich country in 19th century economic thought. We also review the current literature on economic nationalism, and find that alternative perspectives emerge from differing views on the benefits and drawbacks of globalisation. We argue that List's approach remains relevant to understanding contemporary economic nationalism because it highlights a historical context in which the adverse distributional implications of foreign trade are likely to provoke nationalist sentiment. © 2018 Inderscience Enterprises Ltd.
Keywords: Distribution; Economic liberalism; Economic nationalism; Free trade; Globalisation; History; Inequality; International economics; List; Malthus; Protectionism; Ricardo; dept.eco; peer-reviewed